1990
DOI: 10.1152/jappl.1990.68.4.1494
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hyperoxemia and ritanserin on skeletal muscle microflow

Abstract: Serotonin2 (5-HT2) receptor antagonists (ketanserin, ritanserin) can normalize a hyperoxemia-induced disturbance in skeletal muscle oxygenation, presumably by local microflow changes. The purpose of this study was to develop equipment for local hydrogen clearance measurements with a modified eight-channel platinum electrode to assess changes in local skeletal muscle capillary blood flow induced by hyperoxemia and ritanserin (0.035 mg/kg) during hyperoxemia. Laser-Doppler flowmetry was used for regional microfl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…[1,5,7] Moreover, in several investigations in which tissue oxygenation was studied, decreased oxygenation, sometimes even to hypoxic levels, together with signs of maldistribution of capillary flow were found as a response to hyperoxemia. [5,[11][12][13] Another deleterious effect of hyperoxemia was reported by Pizov et al [4] in which they determined there was a larger increase of proinflammatory cytokines in patients treated with 100% oxygen compared with the 50% oxygen group. A delayed recovery in patients treated with 100% oxygen was reported in our study.…”
Section: Discussionmentioning
confidence: 84%
“…[1,5,7] Moreover, in several investigations in which tissue oxygenation was studied, decreased oxygenation, sometimes even to hypoxic levels, together with signs of maldistribution of capillary flow were found as a response to hyperoxemia. [5,[11][12][13] Another deleterious effect of hyperoxemia was reported by Pizov et al [4] in which they determined there was a larger increase of proinflammatory cytokines in patients treated with 100% oxygen compared with the 50% oxygen group. A delayed recovery in patients treated with 100% oxygen was reported in our study.…”
Section: Discussionmentioning
confidence: 84%
“…Each LHC wire has a catchment volume radius of 32 pm and thus the sampling resolution is one or two capillaries in skeletal muscle [19], Since the majority of surface vessels in striated muscle are capil laries. the electrode measures mostly flow in capillaries.…”
Section: Comparison O F Flow Resultsmentioning
confidence: 99%
“…the electrode measures mostly flow in capillaries. With an intercapillary' distance of 52 pm [19] and average distance between each measurement channel of 200 pm [22], chances are that each wire is placed over an independent microvascular unit [23], The sam pling volume of LDF is not known, but it is proposed to be one cubic millimeter. Consequently, the measuring volume of the Clark-type surface microelectrode is approximately 1,000 times smaller than that of LDF, and thus there is a difference in the sampling compart ments between the flow methods.…”
Section: Comparison O F Flow Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we have chosen not to have a control group (saline) to the ritanserin period, as it has been shown that the disturbed oxygenation is maintained even after prolonged hyperoxemia [4,8], This excludes that the normalization of P,0;> by the ritanserin injection is a time effect. In addition, in another preparation we have found that ritanserin administration (with a similar dose) during normoxemia did not affect the tissue capil lary perfusion or oxygenation [unpubl.…”
Section: Discussionmentioning
confidence: 99%